A Comparative Psycholinguistic Study on the Subjective Feelings of Well-Being Outcomes of Foreign Language Learning in Older Adults From the Czech Republic and Poland - Klimova, Blanka; Pikhart, Marcel; Cierniak-Emerych, Anna; Dziuba, Szymon; Firlej, Krzysztof (Frontiers in psychology, 2021)
Positive psychology has recently seen unprecedented rise and has reached vast achievements in the area of quality of life (QoL) improvement. The purpose of this study is to show that there are different aspects of well-being that make healthy older people motivated to learn a foreign language at a later age. The research was conducted in the Czech Republic and Poland in two groups of learners aged 55 years and more. The experimental group consisted of 105 Czech respondents who were targeted with an online questionnaire with the aim to determine the level of FLL outcomes connected to QoL in healthy older adults in their L2 acquisition. The second experimental group (n = 100) was established of Polish seniors who attended similar language courses. The findings of the research clearly show that FLL has an irreplaceable role as one of several non-pharmacological strategies utilized to improve the aging process and reduce drawbacks of aging. The results indicate that seniors' overall satisfaction and subjective feelings of well-being are enormously high when attending foreign language classes at older age. FLL, therefore, creates an environment that can enhance QoL of older adults that can be supplemented by other means such as well-balanced diet, other social activities, sport and physical activity, music, or computer games. All these intervention methods can significantly improve QoL of older adults and the parties engaged and/or responsible for taking care of older generation should take it into serious consideration.
Keywords: psycholinguistics; foreign language learning; positive psychology; cognitive linguistics; FLL; elderly people; applied linguistics; L2 acquisition